Hittite local cults - Cammarosano, Michele (Writings from the Ancient World Ser, 2018)
Cover -- Contents -- List of Illustrations -- List of Tables -- Series Editor's Foreword -- Acknowledgments -- Abbreviations -- Signs and Conventions -- Chronological Chart -- Maps -- Introduction -- Local Cults and Cult Management -- Palaeography, Orthography, and Language -- Gods and Cult Images -- The Festivals -- Economics of the Local Cults -- Text Editions -- Bibliography -- Index of Cited Texts